Monitoring chicken livestock process using Vento Application at a farm - Firman Andika; Rachmat Muwardi; Mirna Yunita; Mhd Adanan Purba (Journal of Integrated and Advanced Engineering (JIAE), 2022)
Regular temperature monitoring in the poultry industry is necessary to produce high-quality products. However, the traditional methods of these activities are still massively applied. Therefore, a modest process on poultry farms requires temperature monitoring and control. Vento is a climate controller developed by Big Dutchman that is easy to understand and user-friendly. Further, the module provides a handy installation and operation on the farm. Therefore, Vento is suitable to use in hot climates area. Vento performs temperature control by reading the input collected from the DOL114 sensor and the DOL12 sensor. The DOL114 sensor performs temperature and humidity detection in the front area of the cage. At the same time, the DOL12 was installed to obtain temperature information behind the cage. Both functions as input to operate the Heater, but only the DOL114 sensor is used to activate the cooling pad. The temperature value gathered by the DOL114 sensor and the DOL12 sensor will be processed by Vento, resulting in average temperature data. Thus, the data obtained from the sensor will be transferred to the Vento system to operate the output in the form of an exhaust fan. The exhaust fan serves as a tool that removes air and ammonia in the cage so that the cage temperature complies with a predetermined setpoint.